The Development of Youth Parliamentarism in Africa - SADOVSKAYA Lyubov Mikhailovna (Ученые записки Института Африки Российской академии наук)
The article is devoted to one of the forms of political representation systems development – youth parliamentarism in Africa. It guarantees a balance between power and a society where young Africans are the majority of voters.